NILAI NORMAL LATENSI DAN AMPLITUDO GELOMBANG VISUAL EVOKED POTENTIAL PADA USIA DEWASA - Ade Wijaya,* Manfaluthy Hakim,* Nurhadi Ibrahim,** Joedo Prihartono*** (NEURONA, 2018)
INTRODUCTION VISUAL EVOKED POTENTIALS VEP IS USED TO ASSESS THE VISUAL PATHWAY THROUGH THE OPTIC NERVES AND BRAIN VEP WAVE CAN BE AFFECTED BY PHYSIOLOGICAL AND NONPHYSIOLOGICAL FACTORS SOME OF WHICH CAN BE CONTROLLED WHILE OTHERS CANNOT THUS EACH VEP LABORATORY NEEDS ITS OWN SET OF NORMATIVE VALUES A NORMAL VEP RESPONSE TO A STIMULUS IS A POSITIVE OCCIPITAL PEAK THAT OCCURS AT A MEAN LATENCY OF 100MS MOST OF THE PUBLISHED NORMAL VALUE ORIGINATED FROM ABROAD WHERE DEMOGRAPHICAL AND ENVIRONMENT CONDITION ARE CONSIDERED LESS APPROPRIATE WITH INDONESIAN POPULATION